Performance evaluation of multicell coordinated beamforming approaches for OFDM systems - Assunção, J. (2013)
In this paper we propose and evaluate multicell coordinated beamforming schemes for the downlink of MISO-OFDM systems. The precoders are designed in two phases: first the precoder vectors are computed in a distributed manner at each BS considering two criteria, namely distributed zero-forcing and virtual signal-to-interference noise ratio. Then the system is optimized through distributed power allocation under per-BS power constraint. The proposed power allocation scheme is designed based on minimization of the average bit error rate over all the available subcarriers. Both the precoder vectors and the power allocation are computed by assuming that the BSs have only knowledge of local channel state information and do not share the data symbols. The performance of the proposed schemes are evaluated, considering typical pedestrian scenarios based on LTE specifications. The results have shown that the proposed distributed power allocation scheme outperform the equal power allocation approach.